2014
DOI: 10.1590/0103-6440201302257
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Activity and Synergism of Lactoferrin and Lysozyme Against Cariogenic Microorganisms

Abstract: The present study evaluated the antimicrobial in vitro effects of the salivary proteins lactoferrin and lysozyme on microorganisms involved in the carious process, obtaining their minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC). Streptococcus mutans (ATCC 25175) and Lactobacillus casei (ATCC 7469) were submitted to broth macrodilution of lysozyme at 80 mg/mL and lactoferrin at 200 mg/mL. The tubes were read in a spectrophotometer after they had been incubated at 37 °C for 18… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 24 publications
4
20
0
Order By: Relevance
“…We found that the SP1 showed a broad antimicrobial activity against important pathogens such as S. aureus and P. aeruginosa but it acts at high concentration (12.5 or 6.2 mg/ml) against planktonic forms of these two microorganisms. Such weak activity is comparable to that reported for a different Echinoderm, Holothuria tubulosa (Schillaci et al [ 2013 ]) and to that of some described innate human defence protein like lactoferrin in vitro (de Andrade et al [ 2014 ]). MD results suggest that the observed weak activity could be due to the low stability of SP1, in fact, as showed in RMSD plot (Figure 2 ), the molecule is stable only in a limited time period and in this period it can present the active conformation of Figure 1 .…”
Section: Discussionsupporting
confidence: 86%
“…We found that the SP1 showed a broad antimicrobial activity against important pathogens such as S. aureus and P. aeruginosa but it acts at high concentration (12.5 or 6.2 mg/ml) against planktonic forms of these two microorganisms. Such weak activity is comparable to that reported for a different Echinoderm, Holothuria tubulosa (Schillaci et al [ 2013 ]) and to that of some described innate human defence protein like lactoferrin in vitro (de Andrade et al [ 2014 ]). MD results suggest that the observed weak activity could be due to the low stability of SP1, in fact, as showed in RMSD plot (Figure 2 ), the molecule is stable only in a limited time period and in this period it can present the active conformation of Figure 1 .…”
Section: Discussionsupporting
confidence: 86%
“…Proteins such as lysozymes, interleukins, mucins, and lactotransferrin (LTF) can promote cell aggregation, inhibition, and/or bacterial adherence. 4,5,6,7 Other proteins, such as beta defensins, have…”
mentioning
confidence: 99%
“…Researcher de Andrade FB et al [19] found that bactericidal and bacteriostatic effects of lysozyme against S. mutans were 68.5 mg/mL (MBC concentrations) and 58.7 mg/mL. Other studies found that concentrations of lysozyme required to inhibit biofilm formation is 50-200 μg/ml [47].…”
Section: Advances In Health Science Research Volumementioning
confidence: 99%
“…The main salivary immune factor is secretory IgA (sIgA) [17], while non-immune factors in saliva include lysozyme, lactoferrine, salivary peroxidase, aglutinin, histatine, cystatine, secretory leucocyte proteinase inhibitor (SLPI), defensine-2, chromogranine A, cathelicidine, mucine, and prolin-rich glycoproteins [18]. Lysozyme is one of innate immune saliva and body's first defense and prominent in the oral cavity [18,19].…”
Section: Introductionmentioning
confidence: 99%